TINGKAT PENGETAHUAN MASYARAKAT MENGENAI HUKUM PEMERIKSAAN GIGI DAN MULUT PADA SAAT PUASA RAMADHAN - Abdi, Muhammad Jayadi; Salzabilah, Salzabilah; Hatta , Mohd.; Nurlaili, Nurlaili; Musahib, Yaumil Fadhilah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
In general, fasting is the act of abstaining from food and fluids; according to Islamic law, fasting is defined as abstaining from anything that can break the fast, such as eating and drinking from sunrise to sunset. Muslims limit activities that can break the fast, such as swallowing water or fluids while undergoing dental treatment, which has an impact on the community's dental and oral health. Objective: To determine the level of public knowledge regarding the law of dental and oral examinations during the fasting month of Ramadan. Method: This study is a finding that uses analytical observation with a descriptive correlational research design and a cross-sectional study method. This study was conducted on December 20, 2024 involving teachers of SD Sudirman 4 Makassar. The sampling technique was total sampling with a sample size of 30 respondents. The instruments used were a pre-test questionnaire of 5 questions and a post-test of 5 questions as a measuring tool. Results: Based on the results of the t-test, it is known that the level of public knowledge regarding the law of dental and oral examination during the fasting month of Ramadan with an average of 7.63 and increased after the provision of material, namely 10.00 and a sig value of 0.000 <0.05 was obtained. Conclusion: From the findings, it can be concluded that there is an increase in knowledge from teachers at SD Sudirman 4 Makassar regarding the law of dental and oral examination during the fasting month of Ramadan.